Pulmonary static inflation with 50% xenon attenuates decline in tissue factor in patients undergoing Stanford type A acute aortic dissection repair - Pan, Xudong; Lu, Jiakai; Cheng, Weiping; Yang, Yanwei; Zhu, Junming; Jin, Mu (Journal of thoracic disease, 2018)
The Stanford type A acute aortic dissection (AAD) carries a high risk of mortality and morbidity, and patients undergoing AAD surgery often bleed excessively and require blood products and transfusions. Thus, we studied how xenon alters coagulation using thromboelastography (TEG) and conventional hemostatic tests for patients with AAD undergoing aortic arch surgery involving cardiopulmonary bypass (CPB)/deep hypothermic circulatory arrest (DHCA). This prospective single-center nonrandomized controlled clinical trial, registered in the Chinese Clinical Trial Registry (ChiCTR-ICR-15006435), assessed perioperative clinical variables and serological results from 50 subjects undergoing pulmonary static inflation with 50% nitrogen/50% oxygen from January 2013 to January 2014 and 50 subjects undergoing pulmonary static inflation with 50% xenon/50% oxygen from January 2014 to December 2014 during CPB for Stanford type A AAD. Repeated measures ANOVA were used to identify the effects of xenon on coagulation after surgery. The primary endpoint was perioperative changes in coagulation and fibrinolysis after intubation and 10 minutes, and 6 hours after the operation. The secondary endpoint was to assess the perioperative changes in serum level of tissue factor (TF), tissue factor pathway inhibitor (TFPI) and tissue plasminogen activator (tPA) after intubation and 10 minutes, and 6 hours after the operation. Mean prothrombin time (PT), activated partial thromboplastin time (APTT), international normalized ratio (INR), median fibrinogen degradation product (FDP), and D-dimer peaked and then decreased over 6 hours after surgery. TEG followed a similar trend. From the start to the end of surgery and until 6 h after surgery, mean TF decreased in controls (β -2.61, P<0.001 and β -2.83, P<0.001, respectively), but was maintained relatively stable in xenon group (β -0.5, P<0.001 and β -0.96, P<0.001, respectively). Deterioration of coagulation function and activated fibrinolysis was confirmed by conventional tests and TEG analysis after Stanford type A AAD repair. Pulmonary static inflation with 50% xenon attenuates decline in TF in patients undergoing Stanford type A AAD repair.